(untitled) (Contemporary Journal of Social Science Review, 2024)
Cross-cultural communication is crucial in today’s globalized world. This study examines the pragmatic competency of non-native English speaker by taking Shashi Tharoor’s impactful lecture at the Oxford Union as an example. Tharoor, an Indian diplomat and politician, who is regarded as the Noam Chomsky of India by the media outlets like The Hindu, News 18 and The Wire due to his work in linguistics and social criticism, delivered a thought-provoking address that pinpoints the legacy of British colonialism in India and highlighting the historical context in educational setting. The analysis focuses on Tharoor’s strategic use of various speech acts, such as representatives, expressive, and directives, to enhance his pragmatic competence and persuasive strategies implied behind words. Qualitative Descriptive research methodology has been used to quantify the results. The theoretical framework of the research is Austin’s (1962) and Searle’s (1969) classification of the speech acts to identify the category of the Speech Acts to find the Pragmatic Competence. The study reveals that, despite being a non-native English speaker, Tharoor demonstrates an impressive level of pragmatic ability. He adeptly notices the contextual factors such as the audience who are listening to his speech, occasion, and dominant historical narratives by adapting his vocabulary accordingly. Tharoor’s thorough awareness of linguistic and cultural nuances, as well as his ability to apply suitable pragmatic methods has allowed him to effectively engage the audience and present a persuasive argument. The findings of this study highlight more horizons to work on the pragmatic competence of non-native English speakers, challenging the widely held aspect that language skill alone defines effective cross-cultural communication.